Konsep OVOP Untuk Mengidentifikasi Produk Unggulan Daerah (Studi Kasus Wajik Tapai Melayu) - Sri Maryanti; Nining Sudiar; Afred Suci; Hardi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Abstract In this study, One Village One Product (OVOP) was used to analyze regional development with the aim of advancing the economy of a region through the identification of superior products in the area. The purpose of using One Village One Product (OVOP) is to identify regional superior products, identify market potential and identify regional superior product development strategies using SWOT analysis of Wajik Tapai Melayu food product. The results of this study is that there are several products that can be used as regional superior products in Riau, such as Wajik Tapai Melayu food product. This is also supported by the Government of Riau Province which is now proclaiming the development of tourism objects in Riau to attract more tourists to visit Riau. By increasing tourists to Riau will give an impact on the growth of small industries, such as Wajik Tapai Melayu food products which are also Regional Superior Products in Riau. Keywords: Regional Superior Products, Riau Malay Tape Diamond, SWOT Analysis, One Village One Product (OVOP) Abstrak Dalam penelitian ini digunakan One Village One Product (OVOP) yang bertujuan untuk menganalisis pembangunan daerah dengan tujuan memajukan ekonomi suatu daerah melalui identifikasi produk unggulan yang ada didaerah tersebut. Adapun tujuan menggunakan One Village One Product (OVOP) adalah untuk mengidentifikasi terhadap produk unggulan daerah, mengidentifikasi potensi pasar dan mengidentifikasi strategi pengembangan produk unggulan daerah menggunakan analisia SWOT terhadap produk pangan Wajik Tapai Melayu. Hasil dari penelitian ini adalah ada beberapa produk yang bisa dijadikan produk unggulan daerah di Riau salah satunya adalah produk pangan Wajik Tapai Melayu. Hal ini juga didukung oleh Pemerintah Propinsi Riau saat ini mencanangkan pengembangan objek wisata di Riau untuk menarik wisatawan untuk berkunjung ke Riau, dengan meningkatnya wisatawan ke Riau akan berdampak terhadap pertumbuhan industri kecil salah satunya produk pangan Wajik Tape Melayu yang juga menjadi Produk Unggulan Daerah di Riau.